Ultrasound of the Lateral Femoral Cutaneous Nerve: A Review of the Literature and Pictorial Essay. (13th August 2021) - Becciolini, Marco; Pivec, Christopher; Riegler, Georg
Abstract : We review the ultrasound (US) findings in patients who present with meralgia paresthetica (MP). The anatomy of the lateral femoral cutaneous nerve at the level where the nerve exits the pelvis and potential entrapment sites that can lead to MP are discussed. A wide range of pathological cases are presented to help in recognizing the US patterns of MP. Finally, our experience with US‐guided treatment is discussed.